2019
DOI: 10.3390/jmmp3010017
|View full text |Cite
|
Sign up to set email alerts
|

Process Stability during Laser Beam Welding with Beam Oscillation and Wire Feed

Abstract: Beam oscillation in laser material processing makes it possible to influence process behavior in terms of energy distribution, stability, melt pool dynamics and solidification. Within the setup presented here, the beam is oscillated transverse to the welding direction, and the filler wire is fed to the melt pool of a butt joint with an air gap. One advantage of this setup is the large gap bridging ability. Certain parameter sets lead to the so-called buttonhole welding method, which allows laser welding of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Alderlink [11] carried out a laser welding experiment on a 1.1 mm thick AA5182 plate and found that the gap size accounting for ∼ 50% of the plate thickness can be welded by wire feeding, as opposed to 33.3% without feeding treatment. Schultz [12] successfully conducted the laser tailor-welding process of a 1.5 mm thick AW-6082 plate with a reserved air gap of 1.0 mm, where the filler wire was fed coaxially and was meanwhile swung horizontally (vertical to the traveling direction) to compensate for the uneven deposition of metal drop. Furthermore, Huang et al [13] undertook laser-MIG arc hybrid welding and suggested that the gap-bridging ability could be highly improved with larger laser-wire distance and higher wire feed speed either while maintaining the process stability.…”
Section: Introductionmentioning
confidence: 99%
“…Alderlink [11] carried out a laser welding experiment on a 1.1 mm thick AA5182 plate and found that the gap size accounting for ∼ 50% of the plate thickness can be welded by wire feeding, as opposed to 33.3% without feeding treatment. Schultz [12] successfully conducted the laser tailor-welding process of a 1.5 mm thick AW-6082 plate with a reserved air gap of 1.0 mm, where the filler wire was fed coaxially and was meanwhile swung horizontally (vertical to the traveling direction) to compensate for the uneven deposition of metal drop. Furthermore, Huang et al [13] undertook laser-MIG arc hybrid welding and suggested that the gap-bridging ability could be highly improved with larger laser-wire distance and higher wire feed speed either while maintaining the process stability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increasing the oscillation width and frequency can result in more signi cant mitigation of weld porosity and consequently higher joint strength [19]. Schultz [20] proposed the oscillation as a mean for evenly distributing the energy on the tip of the ller wire. Some researchers have focused on the effect of ller wire and laser oscillating on the weld formation, grain growth, molten pool behavior and defect suppression and both methods can effectively improve the weld quality in terms of: (a) deal with gaps, misalignments, differences in thickness, (b) reduce pore formation and (c) reduce crack susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [6] investigated the importance of wire-laser beam mutual position and distance for promoting a stable melt pool and a smooth wire melting. Schultz et al [7] proposed the oscillation of a high brilliance laser beam as a mean for evenly distributing the energy on the tip of the filler wire instead of defocusing or using a low brilliance beam with a large spot. They also demonstrated that this technique can also have beneficial effects in gap bridging.…”
Section: Introductionmentioning
confidence: 99%